Examining the Role of Social Network on Opportunity Recognition: A Propose Framework - Zakaria, Norria; Ahmad, Mohamad Zaki; Abdullah, Sahadah (2017)
The fundamental activity of entrepreneurship is new venture creation.Therefore, one of the major components of any entrepreneurial venture is the recognition of the opportunity by the entrepreneur.Identifying and selecting the right opportunities for new venture are among the most significant abilities of successful entrepreneur. Hence, explaining the discovery and development of opportunities per se is a key part of entrepreneurship research.This paper builds on the existing theoretical background of opportunity recognition and aimed at investigating the role of entrepreneur’s prior social network towards bridging to information sources that would help entrepreneurs recognizing opportunity.